A contribution to the human capital investment debate vis-à-vis economic growth: The case for Nigeria - Lasbrey Anochiwa (Annals of Human Resource Management Research, 2021)
Purpose: Human capital development is vital for enhancing economic growth, and Nigeria needs to grow. This study investigates the contribution of human capital to Nigeria’s growth. Research Methodology: We disaggregated the article's variables into different models to obtain better results. We employed the Autoregressive Distribution Lag (ARDL) framework to examine the relationship between the variables. Results: The results show that there exists a long-run relationship between human capital indices, education, health, and economic growth in Nigeria. Although the coefficient is positive, it has a statistically insignificant relationship with human capital development and economic growth. Conclusions: Government spending on education and human capital development has a positive but insignificant impact on economic growth in both the short and long run, indicating insufficient investment. This highlights the need for stronger government focus on education and health to support sustainable economic growth. Limitations: The study was hindered by the limited availability and accessibility of reliable data, which may affect the accuracy and generalizability of the findings. Contributions: It is satisfactory to know from this study that human capital is still relevant in explaining growth in Nigeria.